On the fossil alga Elianella elegans PFENDER & BASSE, 1948, and its so-called lookalikes, with description of Elianella brasiliana n.sp Revision of the Juliette PFENDER Collection. Part 1 - Granier, Bruno [UNESP]; Dias-Brito, Dimas [UNESP] (Carnets Geologie, 2016)
According to some authors, the three fossil algal forms discussed in this paper, Cordilites cretosus (REUS, 1846), Elianella elegans PFENDER & BASSE, 1948, and Parachaetetes asvapatii PIA in RAO & PIA, 1936, are synonyms. However, we document that they represent three discrete species. The genus Elianella PFENDER & BASSE, 1948, gets unique features that make it easy to discriminate; we describe a new species from Albian limestones of Brazil. The other two genera, Cordilites POCTA, 1887, and Parachaetetes DENINGER, 1906, share some common features, such as having a thallus made of a lattice-network with columns (filaments) and rows. However, on the basis of their diagnostic criteria, the species Cordilites cretosus and Parachaetetes asvapatii should not be confused.
Keywords: Rhodogorgonales; Elianellaceae; Solenoporacea; Cordilites; Elianella; Parachaetetes